CIFOR's Role in Research Collaboration : Learning from Partners' Perspectives - Bose, Purabi (2012)
In recent years, the notion of doing research with multiple partners has become an important concept in international development. This reflects the belief that partnerships are important for solving complex problems, reducing costs and competition for the same resources, increasing efficiency and ownership, and ensuring greater accountability. The Center for International Forestry Research (CIFOR) was established in 1993 by the Consultative Group on International Agricultural Research (CGIAR) in response to global concerns about the social, environmental and economic consequences of forest loss and degradation. CIFOR's statutes define its mission as 'to contribute to the sustained well-being of people in developing countries, particularly in the tropics, through collaborative strategic and applied research and related activities in forest systems and forestry, and by promoting the transfer of appropriate new technologies and the adoption of new methods o/social organizations, for national development: CIFOR research produces the knowledge and methods needed to improve the well-being of forest-dependent people and to help tropical countries manage their forests wisely for sustained benefits. This research is undertaken in partnership. At any given time, more than 100 developing-country researchers participate in CIFOR research projects. This publication is an initial attempt to explore partners' experience of carrying out research in collaboration with CIFOR. The first part of the document introduces CIFOR's collaborative strategy and the partnership framework used for this study. 'The second section presents the study's objectives, approach and findings. The third and final section analyses the results and the implication of the study's findings for CIFOR and its partners.